2010
DOI: 10.1182/blood-2009-10-230060
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 is constitutively phosphorylated on serine 727 residues, binds DNA, and activates transcription in CLL cells

Abstract: Chronic lymphocytic leukemia (CLL) is the most common leukemia in the Western hemisphere, but its pathogenesis is still poorly understood. Constitutive tyrosine phosphorylation (p) of signal transducer and activator of transcription (STAT) 3 occurs in several solid tumors and hematologic malignancies. In CLL, however, STAT3 is constitutively phosphorylated on serine 727, not tyrosine 705, residues. Because the biologic significance of serine pSTAT3 in CLL is not known, we studied peripheral blood cells of 106 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
264
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(279 citation statements)
references
References 52 publications
12
264
3
Order By: Relevance
“…However, other investigators suggested that STAT3 serine phosphorylation is associated with increased nuclear translocation and serves to maximize transcriptional activity (6,64). Hazan-Halevy et al reported that constitutive phosphorylation of STAT3 on Ser727 residues is a critical event in chronic lymphocytic leukemia (CLL) and may serve as a potent therapeutic target (64).…”
Section: Discussionmentioning
confidence: 99%
“…However, other investigators suggested that STAT3 serine phosphorylation is associated with increased nuclear translocation and serves to maximize transcriptional activity (6,64). Hazan-Halevy et al reported that constitutive phosphorylation of STAT3 on Ser727 residues is a critical event in chronic lymphocytic leukemia (CLL) and may serve as a potent therapeutic target (64).…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the molecular events that determine the effect of dinaciclib on CLL cell survival, we measured the activation status of multiple pro-survival oncogenic signalling pathways that have been reported to be upregulated in B cell malignancies, such as STAT3, NF-κB, p38, PI3K/AKT and RAF/MEK/ERK (Cuní, et al 2004, Hazan-Halevy, et al 2010, Kawauchi, et al 2002, Ogasawara, et al 2003, Pickering, et al 2007, Ringshausen, et al 2002, Rozovski, et al 2014, Sainz-Perez, et al 2006. The phosphorylation level of STAT3 (Tyr705), IκBα (Ser32/36), p38 (Thr180/Tyr182), AKT (Ser473) and ERK (Thr202/Tyr204) were assessed as markers of activation of these pathways in MEC-1.…”
Section: Dinaciclib Inhibits Pro-survival Signals In Cll Cellsmentioning
confidence: 99%
“…NF-κB RelA/p65 activation correlates chemoresistance and poorer clinical outcome in CLL (Cuní, et al 2004, Furman, et al 2000. Moreover, NF-κB activation can be regulated by STAT3 (Liu, et al 2011), which is constitutively phosphorylated at serine 727 in CLL cells (Hazan-Halevy, et al 2010, Rozovski, et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We next studied AKT isoform activation in the context of the oncogene STAT3 , a factor of clinical significance to CLL, which has been described to directly interact with the AKT1 promoter (Park et al , 2005; Hazan‐Halevy et al , 2010). Activation of CLL cells by T cells resulted in pronounced STAT3 signalling (pY(705)‐STAT3), which could be antagonised by treatment with the STAT3 inhibitor S3I‐201 (Fig 2C).…”
mentioning
confidence: 99%